Advances in Computing Applications - Chakrabarti, Amlan; Sharma, Neha; Balas, Valentina Emilia (Springer Nature Singapore : Imprint: Springer, 2016)
This edited volume presents latest high-quality technical contributions and research results in the areas of computing, informatics, and information management. The book deals with state-of-the-art topics, discussing challenges and possible solutions, and explores future research directions. The main goal of this volume is not only to summarize new research findings but also place these in the context of past work. This volume is designed for a professional audience, composed of researchers, practitioners, scientists and engineers in both academia and the industry.